Large deformations in oriented polymer glasses: experimental study and a new glass-melt constitutive model - De Focatiis, Davide S.A.; Embery, John; Buckley, C.Paul (Wiley, 2010)
An experimental study was made of the effects of prior molecular orientation on large tensile deformations of polystyrene in the glassy state. A new hybrid glass-melt constitutive model is proposed for describing and understanding the results, achieved by parallel coupling of the ROLIEPOLY molecularly-based melt model with a model previously proposed for polymer glasses. Monodisperse and polydisperse grades of polystyrene are considered. Comparisons between experimental results and simulations illustrate that the model captures characteristic features of both the melt and glassy states. Polystyrene was stretched in the melt state and quenched to below Tg, and then tensile tested parallel to the orientation direction near the glass transition. The degree of strain-hardening was observed to increase with increasing prior stretch of molecules within their entanglement tubes, as predicted by the constitutive model. This was explored for varying temperature of stretching, degree of stretching, and dwell time before quenching. The model in its current form, however, lacks awareness of processes of subentanglement chain orientation. Therefore, it under-predicts the orientation-direction strain hardening and yield stress increase, when stretching occurs at the lowest temperatures and shortest times, where it is dominated by subentanglement orientation.